Pancreatic Ductal Morphogenesis and the Pdx1 Homeodomain Transcription Factor - Wescott, Melanie P. (The American Society for Cell Biology, 2009)
Embryonic development of the pancreas is marked by an early phase of dramatic morphogenesis, in which pluripotent progenitor cells of the developing pancreatic epithelium give rise to the full array of mature exocrine and endocrine cell types. The genetic determinants of acinar and islet cell lineages are somewhat well defined; however, the molecular mechanisms directing ductal formation and differentiation remain to be elucidated. The complex ductal architecture of the pancreas is established by a reiterative program of progenitor cell expansion and migration known as branching morphogenesis, or tubulogenesis, which proceeds in mouse development concomitantly with peak Pdx1 transcription factor expression. We therefore evaluated Pdx1 expression with respect to lineage-specific markers in embryonic sections of the pancreas spanning this critical period of duct formation and discovered an unexpected population of nonislet Pdx1-positive cells displaying physical traits of branching. We then established a 3D cell culture model of branching morphogenesis using primary pancreatic duct cells and identified a transient surge of Pdx1 expression exclusive to branching cells. From these observations we propose that Pdx1 might be involved temporally in a program of gene expression sufficient to facilitate the biochemical and morphological changes necessary for branching morphogenesis.